2010
DOI: 10.1523/jneurosci.6027-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Glia Contribute to the Purinergic Modulation of Inspiratory Rhythm-Generating Networks

Abstract: Glia modulate neuronal activity by releasing transmitters in a process called gliotransmission. The role of this process in controlling the activity of neuronal networks underlying motor behavior is unknown. ATP features prominently in gliotransmission; it also contributes to the homeostatic ventilatory response evoked by low oxygen through mechanisms that likely include excitation of preBötzinger complex (preBötC) neural networks, brainstem centers critical for breathing. We therefore inhibited glial function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 55 publications
9
101
0
1
Order By: Relevance
“…While these findings suggest that astrocytes do not directly modify neuronal activity in the pre-Bö tC, astrocytes may nonetheless be important for the maintenance of the respiratory rhythm generation in this complex. For instance, the astrocyte inhibitor methionine sulfoximine depresses breathing in vivo (Young et al, 2005), and glial inhibitors (fluorocitrate, fluoroacetate, and methionine sulfoximine) reduce respiratory-related activity in the preBö tC in vitro (Erlichman et al, 1998;Huxtable et al, 2010). We have not examined such inhibition of astrocytes in the present study.…”
Section: Resultsmentioning
confidence: 91%
“…While these findings suggest that astrocytes do not directly modify neuronal activity in the pre-Bö tC, astrocytes may nonetheless be important for the maintenance of the respiratory rhythm generation in this complex. For instance, the astrocyte inhibitor methionine sulfoximine depresses breathing in vivo (Young et al, 2005), and glial inhibitors (fluorocitrate, fluoroacetate, and methionine sulfoximine) reduce respiratory-related activity in the preBö tC in vitro (Erlichman et al, 1998;Huxtable et al, 2010). We have not examined such inhibition of astrocytes in the present study.…”
Section: Resultsmentioning
confidence: 91%
“…7E does not. Since it has been suggested that NE and ATP evoke Ca 2ϩ signals selectively in astrocytes (Duffy and MacVicar 1995;Fu et al 2013;Huxtable et al 2010), the recordings in Fig. 7E may originate from a neuron and those in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes in the brainstem chemoreceptor area are highly chemosensitive; they respond to decreases in pH with increases in [Ca 2ϩ ] i and release of ATP, which led to activation of chemosensitive neurons and induced adaptive increases in breathing . It was demonstrated that PBC glia also respond to ATP, with increased [Ca 2ϩ ] i and glutamate release, and may therefore contribute to the ATP sensitivity of PBC networks and possibly to the hypoxic ventilatory response (Huxtable et al, 2010).…”
Section: Central Control Of Respirationmentioning
confidence: 99%